The Effects of Perception on School Environment and Vocabulary Mastery towards Students’ Reading Comprehension - Muhamad Iqbal Fauzi; Lilik Yuliawati (Journal of English Language Learning, 2023)
Reading is a fundamental skill that must be mastered in learning English as foreign language. There are many factors which can influence students’ reading comprehension. This study aims to examine the effects of perception on school environment and vocabulary mastery towards students’ reading comprehension in the State of Senior High School in Tangerang Banten. Population in this research is 11th grade students of State Senior High School in Kota Tangerang Banten. The samples of the research were taken as much as 60 respondents from two schools of one sub-district with A accredited. The data were collected by giving two sets of objective test and one set of questionnaire as the instruments to the 60 students. The results showed that 1) there is positive effect of perception on school environment and vocabulary mastery simultaneously towards students’ reading comprehension; 2) there is positive effect of perception on school environment towards students’ reading comprehension; 3) there is positive effect of vocabulary mastery towards students’ reading comprehension. Keyword: Perception on School Environment, Vocabulary Mastery, Reading Comprehension